Procedimientos mínimamente invasivos en nefrourología y patología pelviana - Palavecino R., Patricio; Cabezas R., Mariela; Gutiérrez H., Óscar; Pérez M., Claudio; Tapia L, Mario (Revista Hospital Clínico Universidad de Chile, 2007)
Future medicine tendency is executing minimum invasive procedures in areas such as diagnostic and therapeutic. Nephrourology is not the exception. Simple and complex techniques are analyzed and described at the Interventional Unit of Imaging Center, Hospital Clínico Universidad de Chile, with theoretic and practical basis approved by several national and international institutions.